A Study on the Challenges Faced by Teachers in Implementing the Single National Curriculum - Mirza Arslan Razzaq; Dr. Uzma Batool; Dr. Fareena Nazim; Shamsher Ali Khan (Journal for Social Science Archives, 2025)
The Single National Curriculum (SNC) is a comprehensive educational curriculum that aims to provide a fair and equal opportunity for all students to receive a high-quality education. The present study has one objective. The objective is the reorganization of the challenges faced by Primary School Teachers (PSTs) during the teaching of Single National Curriculum (SNC). The present study targets Primary and Elementary school level and the respondents are primary class teachers. The area of population was based upon one Tehsil i.e. Sohawa (Tehsil of District Jhelum, Punjab). Total population of the study was 520 male and female teachers. A sample of 250 teachers out of 520 teachers (Male & Female) was taken using simple random sampling technique. The data was collected through questionnaire. The questionnaire contains 25 items. The data was analyzed through SPSS version 22. According to the findings, a majority of the respondents agreed that there were several key challenges. The top challenges identified were the implementation of the curriculum, the availability of resources was also noted as a significant challenge, the need for adequate training for teachers to effectively teach the curriculum. Lastly, respondents identified assessment as another challenge faced by teachers during the teaching of the single national curriculum. At the end it is suggested that further studies can indeed be conducted to explore the external factors that influence the single national curriculum (SNC).